2019
DOI: 10.1021/acsomega.8b03461
|View full text |Cite
|
Sign up to set email alerts
|

Direct Monitoring of Microgel Formation during Precipitation Polymerization ofN-Isopropylacrylamide Using in Situ SANS

Abstract: Poly( N -isopropylacrylamide) microgels have found various uses in fundamental polymer and colloid science as well as in different applications. They are conveniently prepared by precipitation polymerization. In this reaction, radical polymerization and colloidal stabilization interact with each other to produce well-defined thermosensitive particles of narrow size distribution. However, the underlying mechanism of precipitation polymerization has not been fully understood. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 55 publications
2
32
0
1
Order By: Relevance
“…Virtanen et al (2019) recently concluded a comparable formation mechanism based on in situ small-angle neutron scattering measurements of the synthesis of PNIPAM-based microgels. 46…”
Section: Resultsmentioning
confidence: 99%
“…Virtanen et al (2019) recently concluded a comparable formation mechanism based on in situ small-angle neutron scattering measurements of the synthesis of PNIPAM-based microgels. 46…”
Section: Resultsmentioning
confidence: 99%
“…The deviation between the conversion and the particle growth kinetics might occur due to reacted monomer not being built into microgel particles, but as a part of oligomers. The absolute values of the rate constants and the total conversion strongly depend on the respective reaction conditions and can be influenced by the monomer properties [66], the addition of accelerators [50], or by surfactants [40]. Furthermore, the progress implies an offset from the origin, indicating the existence of an induction period which could not be accessed here.…”
Section: Kinetics Of Microgel Formationmentioning
confidence: 98%
“…In the context of inline monitoring, prominent vibrations in acrylamides have been used as probes for monomer conversion in batch syntheses, using Raman spectroscopy [49]. Moreover, Virtanen et al [50] studied the microgel formation by in situ SANS in a stopped-flow setup.…”
Section: Introductionmentioning
confidence: 99%
“…It can be noted at first glance that the polymerization rate using the redox initiator systems (NP3 and NP5) is much higher at 40 °C than with merely APS at 60 °C (NP1 and NP2). This is attributable to the much faster initiator decomposition rate in the redox system compared to its thermal homolysis [38,39]. With SBS and TEMED maximum conversion is achieved already after about 40 minutes, while using only APS with and without SDS approximately 120 minutes is needed.…”
Section: Monomer Conversion Measurementsmentioning
confidence: 99%